Retinal Neurovascular Impairment in Non-diabetic and Non-dialytic Chronic Kidney Disease Patients - Zeng, Xiaomin; Hu, Yijun; Chen, Yuanhan; Lin, Zhanjie; Liang, Yingying; Liu, Baoyi; Zhong, Pingting; Xiao, Yu; Li, Cong; Wu, Guanrong; Kong, Huiqian; Du, Zijing; et al. (Frontiers in Neuroscience, 2021)
Background: Widespread neural and microvascular injuries are common in chronic kidney disease (CKD), increasing risks of neurovascular complications and mortality. Early detection of such changes helps assess the risks of neurovascular complications for CKD patients. As an extension of central nervous system, the retina provides a characteristic window to observe neurovascular alterations in CKD. This study aimed to determine the presence of retinal neurovascular impairment in different stages of CKD. Methods: 115 non-diabetic and non-dialytic CKD patients of all stages and a control group of 35 healthy subjects were included. Retinal neural and microvascular parameters were obtained by optical coherence tomography angiography (OCTA) examination. Results: CKD 1-2 group (versus control group) had greater odds of having decreased retinal ganglion cell-inner plexiform layer thickness (GC-IPLt) (odds ratio [OR]: 0.92; 95% confidence interval [CI]: 0.86-0.98), increased ganglion cell complex-focal loss volume (GCC-FLV) (OR: 3.51; 95% CI: 1.27-9.67) and GCC-global loss volume (GCC-GLV) (OR: 2.48; 95% CI: 1.27-4.82). The presence of advanced stages of CKD (CKD 3-5 group versus CKD 1-2 group) had greater odds of having decreased vessel density in superficial vascular plexus (SVP) -Wholelmage (OR: 0.77, 95% CI: 0.63-0.92), SVP-ParaFovea (OR: 0.83, 95% CI: 0.71-0.97), SVP-ParaFovea (OR: 0.76, 95% CI: 0.63-0.91), deep vascular plexus (DVP)-Wholelmage (OR: 0.89, 95% CI: 0.81-0.98), DVP-ParaFovea (OR: 0.88, 95% CI: 0.78-0.99) and DVP-PeriFovea (OR: 0.90, 95% CI: 0.83-0.98). Besides, stepwise multivariate linear regression among CKD patients showed that β2-microglobulin was negatively associated with GC-IPLt (β: -0.294; 95% CI: -0.469 ~ -0.118), and parathyroid hormone was positively associated with increased GCC-FLV (β: 0.004; 95% CI: 0.002~0.006) and GCC-GLV (β: 0.007; 95% CI: 0.004~0.01). Urine protein to creatinine ratio was positively associated with increased GCC-FLV (β: 0.003; 95% CI: 0.001~0.004) and GCC-GLV (β: 0.003; 95% CI: 0.001~0.006). Conclusion: Retinal neuronal impairment is present in early stages of CKD (stage 1-2) and it is associated with accumulation of uremic toxins and higher UACR. While retinal microvascular hypoperfusion, which is associated with worse eGFR, was only observed in relatively advanced stages of CKD (stage 3-5). The results highlight the importance of monitoring retinal neurovascular impairment in different stages of CKD.